Complex partial seizure with postictal aggression as a presentation of atypical eclampsia: a case report - Agrawal, Pawan Kumar Bajaj; Gauchan, B.; Dhungana, S.K.; Wong, L. (Journal of Karnali Academy of Health Sciences, 2018)
Background: Complex partial seizure with sudden onset in near term pregnancy can be challenging to the attending clinician and it is essential to proceed with a presumptive diagnosis of eclampsia, especially in resource poor settings. Unlike generalized tonic clonic seizures, which are more common in eclampsia, complex partial seizures may not jeopardize the fetus with the same severity. However the associated postictal aggression manifested in self-inflicted trauma poses an imminent risk onto the fetus. Case presentation: A nineteen year old gravida two para one living zero woman presented with seizure at thirty six weeks and three days of gestation in a district hospital. The blood pressure recordings during her entire pregnancy were normal and proteinuria was not present. Her previous pregnancy had a similar course, with self-inflicted trauma to her abdomen in a postictal state and resulted in loss of fetus. She did not have any seizures in between then and the current admission. While being managed in the labor ward, the family physicians witnessed complex partial seizure with postictal aggression. The delivery was expedited with caesarean section and she had no further seizure activity. Conclusion: Complex partial seizures with postictal aggression in pregnancy are rare but can be an atypical presentation of eclampsia and poses a diagnostic dilemma to the clinician.